Multiple safety net regulators and agency problems in the EU: is Prompt Corrective Action a partial solution - David G. Mayes; María J. Nieto; Larry Wall (Bank of Finland, 2007)
Prompt Corrective Action (PCA) provides a more efficient mechanism for dealing with problem banks operating in more than one European country. In a PCA framework, a bank's losses are likely to be substantially reduced. This reduction in the losses to deposit insurance and governments will improve the problem of allocating those losses across the various insurance schemes and make it less likely that any deposit insurer will renege on its obligations in a cross-border banking crisis. This paper explores the institutional changes needed in Europe if PCA is to be effective in resolving the cross-border agency problems that arise in supervising and resolving cross-border banking groups. The paper identifies these changes starting with enhancements in the availability to prudential supervisors of information on banking groups' financial condition. Next, the paper considers collective decision-making by prudential supervisors with authority to make discretionary decisions within the PCA framework as soon as a bank of a cross-border banking group falls below the minimum capital standard. Finally, the paper analyses the coordination measures that should be implemented if PCA requires the bank to be resolved.
URN:NBN:fi:bof-20140807484
Keywords: G28; K23; F20; 330; banking supervision; European Union; Prompt Corrective Action